1990
DOI: 10.1093/nar/18.10.3007
|View full text |Cite
|
Sign up to set email alerts
|

Development of a short-term,in vivomutagenesis assay: the effects of methylation on the recovery of a lambda phage shuttle vector from transgenic mice

Abstract: Transgenic mice suitable for the in vivo assay of suspected mutagens at the chromosome level have been constructed by stable integration of a lambda phage shuttle vector. The shuttle vector, which contains a beta-galactosidase (beta-gal) target gene, can be rescued from genomic DNA with in vitro packaging extracts. Mutations in the target gene are detected by a change in lambda phage plaque color on indicator agar plates. Initial rescue efficiencies of less than 1 plaque forming unit (pfu)/100 micrograms of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(40 citation statements)
references
References 21 publications
0
40
0
Order By: Relevance
“…The establishment of transgenic mouse models for the quantitative detection of gene mutations (1,2) has provided unprecedented access to the study of mutagenesis in diverse tissues (3)(4)(5) and provided the basis for the establishment of a gene mutation assay in germ cells that would predict the transmission of induced mutations to subsequent generations. The process of accepting a transgenic mouse model for the detection and enumeration of induced gene mutations must involve the determination that the mutant frequencies (4,6) and the molecular characteristics of the mutations detected are representative of endogenous genes (6).…”
mentioning
confidence: 99%
“…The establishment of transgenic mouse models for the quantitative detection of gene mutations (1,2) has provided unprecedented access to the study of mutagenesis in diverse tissues (3)(4)(5) and provided the basis for the establishment of a gene mutation assay in germ cells that would predict the transmission of induced mutations to subsequent generations. The process of accepting a transgenic mouse model for the detection and enumeration of induced gene mutations must involve the determination that the mutant frequencies (4,6) and the molecular characteristics of the mutations detected are representative of endogenous genes (6).…”
mentioning
confidence: 99%
“…lacZ, lacI or cII have been employed as reporter genes in transgenic rodents, such as the Muta TM mouse, and the Big Blue R mouse and rat. [3][4][5][6][7] Despite differences in size and sequence context, spontaneous mutation frequencies of these reporter genes are in the mid-10 −5 range and those are predominantly base substitutions in most tissues. This high background of base substitutions may make it difficult to detect rare mutations such as deletions induced by ionizing radiation.…”
Section: Overview Of Gpt Delta Transgenic Rodentsmentioning
confidence: 99%
“…It has also been shown that some of these activities inhibit the transfer of lambda shuttle vector DNA from transgenic mice to E. coli cells (14,20,21,45). These inhibitory effects on lambda phage rescue result at least partially from the high levels of eukaryotic cytosine methylation occurring within the DNA (21).…”
mentioning
confidence: 99%
“…It has also been shown that some of these activities inhibit the transfer of lambda shuttle vector DNA from transgenic mice to E. coli cells (14,20,21,45). These inhibitory effects on lambda phage rescue result at least partially from the high levels of eukaryotic cytosine methylation occurring within the DNA (21). We had previously developed restriction-free lambda packaging extracts and plating strains in order to remove the inhibitory effect and increase the efficiency of these processes (21,22,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation